Coronary artery disease prescribing pattern and risk factor assessment in the patients undergoing angioplasty - Solanki, Nilay D.; Patel, Nisha; Desai, Shubha; Patel, Varsha (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Coronary artery disease is caused by an obstruction in vascular supply to the heart. Angioplasty is a frequently used intervention for the management of CAD patients. Supportive and preventive therapies are additionally provided to these patients. Objective of current study was to assess the associated risk factors as well as prescribing trends in CAD patients. Methods: A prospective study was conducted in 88 patients undergoing coronary angioplasty. Patients were assessed for risk factors of CAD. Medication history of patients was recorded in case record form for analysis of prescribing trend and its rationality. Data were statistically analyzed using prism software. Results: In present study most of the CAD patients were male (80.68%) and mean age of patient was 59.19 years. Majority of patients (39.77%) were in age range of 61-70 years. Most common associated conditions at admission were hypertension and diabetes. In this study, BMI, stress, lack of exercise, hypertension, diabetes, family history of CVD were risk factors of CAD and significant correlation observed with risk factors and coronary artery disease. (p<0.05) Frequently prescribed drugs were antiplatelet, antibiotics, antihypertensive, antiulcer, antihyperlipidemic, antidiabetic agents. In 19.31% cases, drug interaction was detected out of which two cases recorded severe. Medical stents coated with everolimus, sirolimus were also prescribed. Conclusions: It was concluded that history of cardiovascular disease, hypertension, diabetes are major risk factors of CAD. Certain level of irrationality in the prescribing trend was observed. Proper patient counselling and care can help in preventing CAD and reduces health burden.